Lighting a Latern in the Storm: The Transformation of Professional and Spiritual Identity of Special Guidance Teachers in Indonesia - Imron Muzakki; Novi Wahyu Winastuti (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Inclusive education in Indonesia places Special Guidance Teachers/GPK in a central position. However, it also burdens them with severe systematic challenges, ranging form competency gaps and role ambiguity to resource limitations, which leads to a high risk of professional burnout. This study aims to analyse the transformative impact of a professional development program themed